The Effect Of Health Promotion Using Word Square Media On Students' Knowledge Of Tuberculosis At Smp Negeri Kota Bengkulu - Tiara Meka Lian (Diagnosa, 2025)
Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis bacteria. The main symptoms of TB include chronic cough lasting more than four weeks, high fever reaching 40–41°C, shortness of breath, and loss of appetite. This study aims to analyze the effect of health promotion using the Word Square media on students' knowledge of TB at SMP Negeri Kota Bengkulu in 2020. The type of research used is a quasi-experimental study with a pretest-posttest group with control design. The sample consisted of 70 students selected through purposive sampling, divided into an intervention group (35 students) and a control group (35 students). The characteristics of the respondents showed that most students were 13 years old, and the majority were female in both groups. The results indicated an increase in the average knowledge score in the intervention group after using the Word Square media (mean = 9.63) compared to the leaflet media in the control group (mean = 7.80). Statistical tests revealed significant differences in the mean knowledge before and after the intervention in both the Word Square group (ρ = 0.000) and the leaflet group (ρ = 0.036). The Word Square media had a greater impact than the leaflet media in improving students' knowledge. Conclusion: Health promotion through Word Square media is effective in enhancing students' knowledge of TB. This media can serve as an innovative alternative in health promotion programs to raise students' awareness of TB.